Optimizing Islamic Financial Instruments in Indonesia to Support SDGs: Maqashid Syariah Perspective - Ahmad Kholil; Muhammad Zuardi; Amrin; Juryatina (Universitas Muhammadiyah Surakarta, 2025)
Objective: Examine how these instruments can be aligned with global development goals while grounded in Islamic principles. This study aims to analyze the optimization of various Islamic financial instruments, such as Zakah, Waqf, Sukuk, and Islamic banking, to support the achievement of SDGs. Theoretical Framework: Maqashid Syariah, which emphasizes the protection of essential human values such as faith, life, intellect, lineage, and wealth, the study highlights the role of Islamic finance in promoting social welfare, economic justice, and environmental sustainability. Literature Review: Conducted, drawing from academic sources, regulatory documents, and practical implementations of Islamic finance in Indonesia and other Muslim-majority countries. Methods: The method used in this study is a qualitative approach with literature study techniques, analyzing relevant literature and Islamic financial policies in Indonesia and the world. Results: The study indicate that Islamic financial instruments can contribute significantly to supporting SDGs, especially in the aspects of poverty alleviation (SDG 1), quality education (SDG 4), economic equality (SDG 10), and sustainable consumption and production (SDG 12). However, there are challenges in optimizing implementation, such as regulations that are not yet uniform, low Islamic financial literacy, and limited innovation in instrument development. Implications: This study recommends synergy between the government, Islamic financial institutions, academics, and the community in strengthening a sustainable Islamic financial ecosystem. With proper optimization, Islamic finance can be an alternative solution in supporting a green, inclusive, and equitable economy by the principles of Maqashid Syariah and the goals of the SDGs. Novelty: This research lies in its integrative approach that bridges the ethical vision of Maqashid Syariah with the contemporary global development agenda, offering a holistic and faith-based framework for sustainable economic progress in Indonesia.